Badminton Learning Model Using Media Rubber Tires And Barbels To Improve Smash Jump Skills In Athletes University Achievement Development Lampung - Pratama, Wahyu Riyan; Surisman, Surisman; Siswoyo, Joan; Tarigan, Herman (Jurnal Pendidikan Jasmani (JPJ), 2024)
Research and development (R&D) is a systematic study process to develop and validate products used in education (Andi Ibrahim et al., 2018). Research and development (R&D) is a systematic study process to develop and validate products used in education (Andi Ibrahim et al., 2018). The development of a smash learning model using rubber tires and barbells to improve jumping smashes for athletes at Lampung University is aimed at producing training models that are effective and more varied. Apart from that, validation data will be presented by four experts, namely badminton experts, learning experts, language experts and media experts obtained through questionnaires.1. Based on the calculation results, the average of the four experts was 84.5%, so this training model was declared valid and suitable for use in supporting the training process for Lampung University athletes.